Assessing the Impact of BPRS Financing on Farmer Empowerment and Food Security in Rural Indonesia - Lestari, Lutfi Bangun; Mafuha, Ilmi (IAIN Manado, 2025)
Islamic Rural Banks (BPRS) hold strategic potential in enhancing food security through inclusive, partnership-based Islamic financing, especially in the agricultural sector, which is a key income source for rural communities. This study aims to analyze the impact of BPRS financing based on murabahah, musyarakah, and mudharabah contracts on farmer empowerment across food security dimensions, including food production, prices, consumption, and stability. A quantitative analysis was conducted using panel data from 154 BPRS sourced from the Financial Services Authority (OJK) covering Q1 2019 to Q4 2023. Static panel models, employing both fixed effects and random effects, were used to determine the best-fit models. The results show that murabahah financing significantly increases food prices (0.055%; p<0.01) and instability (0.070%; p<0.05), while reducing food production (−0.080%; p<0.05) and consumption (−0.574%; p<0.01), indicating its consumptive nature. Musyarakah financing raises food prices (0.021%; p<0.01) and instability (0.023%; p<0.05), but reduces production (−0.029%; p<0.05) and consumption (−0.115%; p<0.01), reflecting its limited productive role. Mudharabah financing significantly reduces food consumption (−0.163%; p<0.01) without significantly affecting production, prices, or stability, suggesting cash flow and business risks for farmers. Macroeconomic factors like regional economic growth (PDRB) reduce production (−0.079%; p<0.10) and instability (−0.187%; p<0.01) while increasing prices (0.018%; p<0.01). These findings underline the importance of reorienting BPRS financing toward more productive, partnership-based schemes for sustainable food security.